Impact of cytochrome P450 2C19 loss-of-function polymorphism on intra-stent thrombi and lesion outcome after everolimus-eluting stent implantation compared to that after first-generation drug-eluting stent implantation. (20th January 2015) - Konishi, Akihide; Shinke, Toshiro; Otake, Hiromasa; Nishio, Ryo; Sawada, Takahiro; Takaya, Tomofumi; Nakagawa, Masayuki; Osue, Tsuyoshi; Taniguchi, Yu; Iwasaki, Masamichi; Kinutani, Hiroto; Masaru, Kuroda; et al.
Abstract: Background: The contribution of clopidogrel response due to cytochrome P450 (CYP) 2C19 loss-of-function polymorphism after drug-eluting stent (DES) implantation is unclear. Methods: A total of 196 patients who had undergone optical coherence tomography (OCT) at 8 months following first-generation DES (120 lesions) and current-generation everolimus-eluting stent (EES) implantation (127 lesions) were enrolled. Patients were divided into 3 groups by CYP2C19 polymorphism: extensive metabolizers (EMs), intermediate metabolizers (IMs), and poor metabolizers (PMs). OCT findings were compared among the 3 groups. Responsiveness to clopidogrel was assessed by VerifyNow platelet reactivity unit (PRU). Results: The incidence of intra-stent thrombi was significantly higher after first-generation DES implantation compared with EES implantation (35% vs 13%, respectively; p = 0.0001). In the first-generation DES group, the incidence of intra-stent thrombi significantly increased among EMs, IMs, and PMs (21% vs 36% vs 63%, respectively; p = 0.007), while there was no significant difference among the 3 groups after EES implantation (10% vs 13% vs 20%, respectively; p = 0.55). The PRU significantly increased among EMs, IMs, and PMs in each stent group. In multivariate analyses, although PMs had a 3-fold higher risk of thrombi formation compared with non-PMs after first-generation DES implantation, there were no significant differences in thrombi formation between the 2 groups after EES implantation. The optimal PRU cutoff values for the prediction of intra-stent thrombi with first-generation DES and EES were 234 and 256, respectively. Conclusion: CYP2C19 loss-of-function polymorphism is associated with a higher incidence of intra-stent thrombi after first-generation DES implantation, while the impact is attenuated following EES implantation.